The construction of negotiation for social harmony in Minangkabau West Sumatra Indonesia - Silfia Hanani; Yustiloviani; Rahman, Ali; Bustamar (Penerbit Universiti Kebangsaan Malaysia, 2021)
Minangkabau is one of the ethnic groups and also the name of their land in West Sumatra, Indonesia. To achieve harmonious life, Minangkabau people practice a negotiation tradition to solve problems and their interrelationship with other ethnic groups. Instead of a new invention, local elites have long-established this negotiation tradition since the declaration of adat basandi syarak, syarak basandi kitabullah (the custom-built upon Islamic law, Islamic law built upon the Quran) as the identity of Minangkabau people. This declaration of identity resulted from the negotiation between local elites and religious elites in the past when they made reconciliation to build harmony together. Thus, the philosophy of adat basandi syarak, syarak basandi kitabullah is a symbol rather than peace because it was formulated after the negotiation process between local and religious elites to end the conflict between them. This negotiation has brought the agreement that guarantees living side by side in harmony and building Minangkabau together. Eventually, the negotiation tradition becomes a daily practice for the Minangkabau community in making every decision and resolving problems in the community. If the decision-making or problem-solving is not carried out through negotiation, it often leads to disharmony in society. The negotiation tradition in the Minangkabau community is strengthened by joint meetings in determining and deciding various issues in which every party in the forum deliberate in creating a mutually acceptable agreement. Understandably, harmonious life can be achieved in a society when negotiation is widely practiced. In the Minangkabau community, the negotiation tradition does not come on its own, but local and religious elites have developed for a long time.